Income loss among the self-employed: implications for individual wellbeing and pandemic policy measures - Stefan Schneck (Review of Economics of the Household, 2021)
Due to the pandemic-induced economic crisis, self-employed individuals are currently suffering considerable income losses. The self-employed and the members in their households usually form an economic unit. As a consequence, the income cuts not only affect the self-employed themselves but also the rest of their household. We used the German Socio-Economic Panel (SOEP) to calculate how much income the self-employed are able to sacrifice to achieve a subjective barely sufficient household income, which we interpret as the minimum level to maintain the standard of living. Our results suggest that full-time self-employed are typically the bread-earners in their households and that, as a consequence, even moderate income losses of the self-employed often lead to problems in maintaining the living standards of their households. Conditional on individual and household characteristics, the self-employed with employees are found to live in households that are less resilient to income losses. Furthermore, a negative correlation between falling short of the barely adequate household income and wellbeing was discovered. Self-employed in households with less than adequate incomes also reported higher concerns about social cohesion. These results have implications for policy - especially in light of the economic crisis induced by the pandemic.
Keywords: 330; L26; Entrepreneurial households; Income; Income cuts; Self-employment